The Translation of Indonesian Passive Voice in Research Articles’ Abstracts into English: Human Vs Machine Translation - Isra F Sianipar; Sajarwa Sajarwa (English Department FBS UNP, 2021)
The existence of abstracts within research articles (RA) is one of the requirements of a published article. When the research is important internationally rather than locally, the abstract should be translated into English. Since lots of passive voice construction was found In Indonesian research articles, this study aims to explore the translation of passive voice in Indonesian RA abstracts into English conducted by human translation and machine translation (google translate). This present study is translational research by applying interpretative qualitative-quantitative analysis. The data in this study were RA abstracts obtained from Journal “Linguistics Indonesia” which was published in 2015- 2021, there are 60 research articles in total. After analyzing those articles with AntConc (a corpus-based analyzing tool), it was found that there are 341 passive voice occurrences in Indonesian research articles. However, in the translated abstract corpus, TERA-HT there are 308 occurrences and in TERA MT with 321 occurrences. Besides the differences in the frequency, there are also some differences in linguistics feature of passive in the translated abstracts, such as 1) The difference in using tenses; 2) The differences in using “Be (Singular/Plural); 3) the difference in using the passive voice construction and 4) Modulation (the change of Passive voice into Active voice). This research also reports that human translation is better than machine translation.